Palbociclib dose reductions and the effect on clinical outcomes in patients with advanced breast cancer. (December 2021) - Ismail, R.K.; van Breeschoten, J.; Wouters, M.W.J.M.; van Dartel, M.; van der Flier, S.; Reyners, A.K.L.; de Graeff, P.; Pasmooij, A.M.G.; de Boer, A.; Broekman, K.E.; Hilarius, D.L.
Abstract: Background: This study aimed to provide insights into the real-world use of palbociclib, dose reductions, and drug effectiveness in (older) patients with advanced breast cancer (BC). Patients and methods: Patients with advanced BC treated with palbociclib from 2017 to 2020 were included. The Kaplan-Meier method was used to calculate time to next treatment (TTNT) and overall survival (OS) for patients with or without dose reductions. These clinical outcomes were also compared in subgroup analyses for older patients (≥70 years) and younger patients (<70 years) and for patients discontinuing palbociclib early (<4 administrations). Results: A total of 598 patients with advanced BC were included, with a median age of 64 years. Palbociclib dose reductions occurred in 33% of all patients. Early discontinuation of palbociclib without dose reductions occurred in 23% of the patients. Patients who required a palbociclib dose reduction were older (median age 67 years vs. 63 years). Patients with dose reductions had a significantly higher TTNT of 16.9 vs. 11.4 months (p < 0.001) and median OS of 29.7 vs. 21.9 months (p = 0.003) compared to patients without dose reductions. The TTNT in older patients was significantly longer (16.9 vs. 11.6 months, p = 0.013) than younger patients, but OS was similar (20.7 vs. 26.7 months, p = 0.051). Conclusion: Palbociclib dose reductions occurred in real-world practice similarly to the PALOMA-3 trial. Patients with dose reductions had no poorer outcomes compared to patients not requiring a dose reduction. Older patients treated with palbociclib had more frequent dose reductions, but this did not appear to affect OS. Highlights: Palbociclib dose reductions occurred in 33% of the real-world patients. Dose reductions did not lead to poorer overall survival. Older patients had more dose reductions, but this did not affect overall survival.